Aspiring to be : the tribal, indigenous condition - Roy Burman, B. K.; Verghese, B. G. (Konark Publishers, 1998)
Papers presented at a Workshop on the Rights of Tribal and Indigenous Peoples held in New Delhi, February 23 to 25, 1996.